Response of optically stimulated luminescence dosimeters subjected to x-rays in diagnostic energy range - Musa, Yahaya; Hashim, Suhairil; Abdul Karim, Muhammad Khalis; Bakar, K. A; Ang, W. C; Salehhon, Nasuha (Institute of Physics Publishing, 2017)
The use of optically stimulated luminescence (OSL) for dosimetry applications has recently increased considerably due to availability of commercial OSL dosimeters (nanoDots) for clinical use. The OSL dosimeter has a great potential to be used in clinical dosimetry because of its prevailing advantages in both handling and application. However, utilising nanoDot OSLDs for dose measurement in diagnostic radiology can only be guaranteed when the performance and characteristics of the dosimeters are apposite. In the present work, we examined the response of commercially available nanoDot OSLD (Al2O3:C) subjected to X-rays in general radiography. The nanoDots response with respect to reproducibility, dose linearity and signal depletion were analysed using microStar reader (Landauer, Inc., Glenwood, IL). Irradiations were performed free-in-air using 70, 80 and 120 kV tube voltages and tube currents ranging from 10 – 100 mAs. The results showed that the nanoDots exhibit good linearity and reproducibility when subjected to diagnostic X-rays, with coefficient of variations (CV) ranging between 2.3% to 3.5% representing a good reproducibility. The results also indicated average of 1% signal reduction per readout. Hence, the nanoDots showed a promising potential for dose measurement in general X-ray procedure.